Cardiac hydatid cyst revealed by ventricular tachycardia - Ibn Elhadj, Zied (2013)
Hydatid disease is a human parasitic infestation caused by the larval stage of Echinococcus Granulosus. The liver and the lungs are the most common locations. Cardiac involvement is rare and accounts for 0.5–2% of all hydatid disease. We report an unusual presentation of cardiac hydatid cyst revealed by ventricular tachycardia in a patient with a history of cerebral hydatid cyst.